2015
DOI: 10.1021/es5052364
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of Dehalobacter and Zerovalent Iron in the Degradation of Chlorinated Methanes

Abstract: The role of bacteria and zerovalent iron (Fe(0)) in the degradation of chlorinated solvents in subsurface environments is of interest to researchers and remediation practitioners alike. Fe(0) used in reactive iron barriers for groundwater remediation positively interacted with enrichment cultures containing Dehalobacter strains in the transformation of halogenated methanes. Chloroform transformation and dichloromethane formation was up to 8-fold faster and 14 times higher, respectively, when a Dehalobacter-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 54 publications
(104 reference statements)
4
32
2
Order By: Relevance
“…This hypothesis is supported by carbon stable isotope ratio data. Recently we found that 12 C/ 13 C fractionation was minimal during TCM respiration by strain UNSWDHB ( ε = −4.3‰) compared CfrA in strain CF ( ε = −28‰) (Chan et al ., ; Lee et al ., ). Masking of the kinetic isotope effect has been show for highly efficient enzymes (Lollar et al ., ), the low enrichment factor indicates a that TmrA is highly efficient at TCM dechlorination compared to CfrA.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This hypothesis is supported by carbon stable isotope ratio data. Recently we found that 12 C/ 13 C fractionation was minimal during TCM respiration by strain UNSWDHB ( ε = −4.3‰) compared CfrA in strain CF ( ε = −28‰) (Chan et al ., ; Lee et al ., ). Masking of the kinetic isotope effect has been show for highly efficient enzymes (Lollar et al ., ), the low enrichment factor indicates a that TmrA is highly efficient at TCM dechlorination compared to CfrA.…”
Section: Resultsmentioning
confidence: 97%
“…Although this comparison is error prone without standardising the concentration of RDases, the data may explain the difference in 13 C/ 12 C fractionation observed during TCM dechlorination by these two strains (i.e. 24.3& 6 0.45& and 227& 6 0.9& for strains UNSWDHB and CF respectively (Chan et al, 2012;Lee et al, 2015). The increased RDase efficiency observed in strain UNSWDHB could lead to masking of the kinetic isotope effect (KIE).…”
Section: Enzyme Kinetics In Cell Free Experimentsmentioning
confidence: 99%
“…CT and CF reduction involves one or two C-Cl bond cleavages in the first rate-limiting step 450 (Elsner et al, 2004;Chan et al, 2012;Lee et al, 2015). For AKIE calculations one C-Cl bond 451 cleavage was assumed and the determined Ɛ values (R 2 ≥0.9) were used (Table 3, Fig.…”
Section: Mechanistic Insights 449mentioning
confidence: 99%
“…In the case of PS, the anaerobic environment that is created following the consumption of the oxidant is ideal for CF microbial dehalogenation under sulfate reduction conditions to be enhanced. Enhanced CF bioremediation has also been observed when combining Fe(0) and methanogens that use the cathodic hydrogen generated by iron corrosion for cometabolic degradation of CF [83][84][85] or even better by dehalorespiring bacteria which are not inhibited at certain concentrations of CF 29 . Therefore, there would be an increasing number of case studies, where CF degradation due to PS application or Although CF anaerobic biodegradation has been reported to occur mainly via cometabolic dechlorination or by dehalorespiration 8 , an alternative pathway was suggested in the presence of cobalamins and involving CF hydrolysis 87,88 .…”
Section: Environmental Significancementioning
confidence: 99%